Enalapril:β-CD complex: Stability enhancement in solid state - Zoppi, Ariana (2011)
Complexation of enalapril maleate with -cyclodextrin was used to overcome the known enalapril maleate–excipient interaction in solid state. The complex formation was characterized by 13C solid state nuclear magnetic resonance, X-ray powder diffraction and scanning electron microscopy. Additionally, thermogravimetric analysis (TGA) was used to evaluate the compatibility between magnesium stearate with enalapril maleate alone or in the complex form. Degradation of the drug at 40 ◦C/75% relative humidity in the presence of magnesium stearate was monitored by high performance liquid chromatography (HPLC). Enalapril maleate in the complex form was more stable than the drug alone, with the drug recovery after 6 month being: 95±1% and 82.1±0.5%, respectively. This satisfactory high stability of the enalapril:-CD complex will be potentially useful for its application as solid pharmaceutical dosage products.